2003
DOI: 10.1521/scpq.18.2.192.21858
|View full text |Cite
|
Sign up to set email alerts
|

A review of life satisfaction research with children and adolescents.

Abstract: An important construct in positive psychology is life satisfaction (LS). Although its importance has been recognized by some school psychologists, research findings have remained unsynthesized. In this article, theory, measurement, and correlates of LS among children and youth are reviewed. Following this review, interrelationships among LS research, positive psychology, and school psychology are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
303
7
34

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 461 publications
(381 citation statements)
references
References 63 publications
22
303
7
34
Order By: Relevance
“…Life satisfaction is an important construct in positive psychology (Gilman and Huebner 2003). Measures of LS are sensitive to the entire spectrum of functioning, and thus, provide indicators of both well-being and psychopathology.…”
Section: Understanding Youth Life Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Life satisfaction is an important construct in positive psychology (Gilman and Huebner 2003). Measures of LS are sensitive to the entire spectrum of functioning, and thus, provide indicators of both well-being and psychopathology.…”
Section: Understanding Youth Life Satisfactionmentioning
confidence: 99%
“…Measures of LS are sensitive to the entire spectrum of functioning, and thus, provide indicators of both well-being and psychopathology. This contrasts with traditional mental health scales that require respondents to indicate the presence or absence of problems, and rate existing problems according to frequency and symptoms, with no option of reporting the characteristics or presence of positive feelings or behaviours (Gilman and Huebner 2003;Kamman et al 1984). Further, as a key indicator of SWB, LS is integral to the science of positive psychology which focuses on identifying strengths and the building of them as buffers against the development of psychopathological problems (Veenhoven 1988).…”
Section: Understanding Youth Life Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associations between the SLSS and demographics (e.g., age, gender) have been typically found as moderate at best in magnitude (e.g., Gilman & Huebner, 2003;Huebner, 1991a). LS is distinguishable from social desirability as the reported correlations have been modest to moderate (e.g., Proctor et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that children starting from the 8-year age are able to differentiate between the basic constituents of subjective well-being: positive affect, negative affect and life satisfaction, as well as correlate them with different spheres of life -family, school, friends, etc. (Gilman & Huebner, 2003). In addition, researchers can't say that life satisfaction as a whole is unequivocally related to satisfaction in various areas.…”
Section: Introductionmentioning
confidence: 99%